Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3390/app7040357
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Performance of Vacuum Membrane Distillation Using Micro-Structured Hydrophobic Aluminum Hollow Fiber Membranes

Abstract: This study develops a micro-structured hydrophobic alumina hollow fiber with a high permeate flux of 60 Lm −2 h −1 and salt rejection over 99.9% in a vacuum membrane distillation process. The fiber is fabricated by phase inversion and sintering, and then modified with fluoroalkylsilanes to render it hydrophobic. The influence of the sintering temperature and feeding temperature in membrane distillation (MD) on the characteristics of the fiber and MD performance are investigated. The vacuum membrane distillatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…The observed reduction of permeate fluxes (Figure 4) as well as LEPw values (Figure 3) with extended grafting time contributed to formation of a smoother surface (Table 1) showing better water-proof character. Summarizing the fabricated hydrophobic membranes possess good transport properties in AGMD compared with literature data [40,42,62,63]. Furthermore, the observed values of permeate fluxes are higher than for ceramic membranes tested in DCMD.…”
Section: Air-gap Membrane Distillation-separation Efficiency Of Modifsupporting
confidence: 56%
“…The observed reduction of permeate fluxes (Figure 4) as well as LEPw values (Figure 3) with extended grafting time contributed to formation of a smoother surface (Table 1) showing better water-proof character. Summarizing the fabricated hydrophobic membranes possess good transport properties in AGMD compared with literature data [40,42,62,63]. Furthermore, the observed values of permeate fluxes are higher than for ceramic membranes tested in DCMD.…”
Section: Air-gap Membrane Distillation-separation Efficiency Of Modifsupporting
confidence: 56%
“…Many authors reported that feed temperature showed a remarkable influence on the permeate flux with ceramic membranes applied to MD, regardless of configuration and feed solution. This propensity is explained by the Antoine equation, which predicts an exponential relationship between the vapor pressure difference and temperature due to the higher latent heat of water evaporation and higher heat transfer coefficient, without affecting the permeate quality.…”
Section: Overview Of Ceramic Membranes Applied To MDsupporting
confidence: 52%
“…Some authors reported that the sintering temperature influenced the wettability behavior after grafting of the prepared ceramic membranes . Lower sintering temperature increased contact angle but decreased LEP.…”
Section: Overview Of Ceramic Membranes Applied To MDmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the polymeric membranes widely adopted in wastewater treatment applications display relatively low thermal and chemical resistance. There has been an upsurge of interest in ceramic membranes for the treatment of high-strength wastewater, for which polymeric membranes are not suitable [4,5]. Ceramic membranes consisting of metal oxides usually exhibit high membrane porosity, membrane permeability, and narrow distribution of the membrane pore size.…”
Section: Introductionmentioning
confidence: 99%